THE RISK FACTORS OF PRIMARY DYSMENORRHEA AMONG FEMALE MEDICAL STUDENTS IN UNIVERSITAS KRISTEN DUTA WACANA, YOGYAKARTA - Ernestine Benita (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Primary dysmenorrhea is menstrual pain which occurs without any underlying pelvic organ diseases. There are several risk factors of dysmenorrhea, which are BMI, age at menarche, smoking habit, and family history. Female medical students are one population with a high risk of having dysmenorrhea with debilitating effect. Objective: To test the association between several risk factors with primary dysmenorrhea in female medical students in Universitas Kristen Duta Wacana (UKDW). Method: This is a cross-sectional study, gathering data from 207 female medical students enrolled in UKDW between September 2018 and January 2019. Further bivariate analyses were performed to test the association between dysmenorrhea prevalence and some risk factors using Chi-square test or Fischer exact test. Results: Out of 207 participants, 158 (76.33%) are diagnosed with primary dysmenorrhea. 31.88 % of the samples are categorised into the underweight, overweight and obese group. The prevalence ratio of underweight and overweight group compared to the normal group resembles U-shape relationship, but not statistically significant (PR = 1.095; p = -.486, and PR 1.055; p = 0.826, respectively). Younger age at menarche (PR = 1.251, p = 0.014) and family history if dysmenorrhea (PR = 1.317; p = 0.002) show a higher prevalence rate compared to normal age group and no family history of dysmenorrhea. Conclusion: Younger age at menarche and family history of dysmenorrhea should be considered as important risk factors, although they are not modifiable. The relationship between body mass index and dysmenorrhea need further investigation with a prospective approach.